The Call for Intellectual Diversity on Campuses and the Problem of Willful Ignorance. Issue 4 (24th November 2020) - Applebaum, Barbara
Abstract : The call for intellectual diversity on college campuses reemerges every few years, fueled by objections to the political imbalance or the liberal slant that conservative commentators claim is characteristic of higher education today. In this article, Barbara Applebaum sets out to add to the debate around intellectual diversity in higher education by addressing it through the lens of epistemic injustice, in general, and, more specifically, willful ignorance. She begins by summarizing the scholarship around epistemic injustice and then provides conceptual resources that are popular on social media to help explain the experience of marginalized knowers. Next, Applebaum demonstrates that unless willful ignorance is taken seriously, these conceptual resources remain unintelligible to dominantly situated knowers. She follows this with a review of some of the scholarship on epistemic injustice and the remedies for this problem proposed in it. Through applying insights gleaned from this scholarship to the call for intellectual diversity, Applebaum concludes that if the call for intellectual diversity is to lead to greater understanding among those who disagree on issues of injustice, it is necessary to confront the problem of willful ignorance in a serious and sustained way.